Fluoromethylcyclopropylamine derivatives as potential in vivo toxicophores – A cautionary disclosure. Issue 4 (15th February 2019) - Acton, Ben; Small, Helen F.; Smith, Kate M.; McGonagle, Alison; Stowell, Alexandra I.J.; James, Dominic I.; Hamilton, Niall M.; Hamilton, Nicola; Hitchin, James R.; Hutton, Colin P.; Waddell, Ian D.; Ogilvie, Donald J.; et al.
Graphical abstract: Abstract: Fluorination of metabolic hotspots in a molecule is a common medicinal chemistry strategy to improve in vivo half-life and exposure and, generally, this strategy offers significant benefits. Here, we report the application of this strategy to a series of poly-ADP ribose glycohydrolase (PARG) inhibitors, resulting in unexpected in vivo toxicity which was attributed to this single-atom modification.